The correlation between the placental pathology and the neurological outcome of neonates ≥ 36 weeks with neonatal encephalopathy treated with therapeutic hypothermia - Abrahams, Ilhaam (Stellenbosch : Stellenbosch University, 2018)
Thesis (MMed)--Stellenbosch University, 2018.